36th Assembly District Assessments
This comparison chart outlines the positions of four 36th Assembly District candidates—Pete Bokron (D), Charles Imbrecht (R), Tom Jolicoeur (D), and Jane Tolmach (D)—on key education and policy issues. The candidates differ on busing, collective bargaining, school finance, tuition increases, and the proposed liquefied natural gas plant in Hueneme, while showing varied approaches to tax reform and teacher evaluation. Tolmach supports busing with financial caution, opposes tuition increases, backs a four-year college in the area, favors income tax reform and property tax rollback, and calls for careful study of LNG hazards. Imbrecht generally supports voluntary busing, tuition increases, and tax adjustments involving federal funds, while Bokron and Jolicoeur take differing Democratic positions on bargaining and taxation. All candidates agree that teachers are best qualified to select instructional materials and methods.